La reversión de la figura del inmigrante y del porteño en las últimas décadas del siglo XX - Marina Sikora (Les Cahiers ALHIM)
The analysis of three plays, Gris de Ausencia (1981) written by Roberto Cossa , Y el mundo vendrá (1989) by Eduardo Rovner and Lejos de aquí (1993) co-written by  Roberto Cossa and Mauricio Kartun, will show that the sainete and the sainete-influenced comedy of the early XXth century stage quite efficiently the social realities of the sixties in Argentina. These types of theatre, popular in the early representation of the immigrant phenomenon, function as the metaphor of the rise of the middle class. As the above mentioned authors re-write the sainete, their goal is to represent the opposite effect of that in the 1920’s, their plays showing the decadence of the early social model.